2017
DOI: 10.29137/umagd.371119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nano-CaCO3 Particles on Shear Strength of Epoxy Resin Adhesives

Abstract: Epoxy resins are a very common type of adhesive materials in several fields like the automotive industry, marine, probably the most important is in the aerospace industry. Adhesive joints of carbon fiber reinforced epoxy composite laminates are worked using an epoxy resin as the adhesive. In this paper, Adhesive joints were modified nano-CaCO3 in order to enhance the shear strength of epoxy adhesives. The enhancements of shear strength of epoxy adhesive joints reinforced with different nano-CaCO3 particles loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Moreover, to increase thermal resistance of epoxy resin, it was examined in [35] to reinforce them with ceramic particles, such as silicon carbide, silica, alumina or silicon nitride. Similar studies were also reported in [36] where nano-CaCO 3 was added to epoxy resin adhesives. However, further studies are necessary to verify the influence of these particles on the radiation properties of the tested traceability system.…”
Section: Resultssupporting
confidence: 84%
“…Moreover, to increase thermal resistance of epoxy resin, it was examined in [35] to reinforce them with ceramic particles, such as silicon carbide, silica, alumina or silicon nitride. Similar studies were also reported in [36] where nano-CaCO 3 was added to epoxy resin adhesives. However, further studies are necessary to verify the influence of these particles on the radiation properties of the tested traceability system.…”
Section: Resultssupporting
confidence: 84%
“…Elastomer nanocomposite reinforced with low volume fraction of nanofillers have created great interest due to their fascinating properties. Nanofillers such as layered silicate clays [1], carbon nano tubes [2], calcium carbonate [3], metal oxides [4] or silica nano particle [5] into elastomer improves significantly the properties such as mechanical, thermal, dynamic mechanical, barrier, flame retardant etc. Typically, nanocomposites are materials having filler size in the nanometer size range, at least in one dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesively-bonded joints (ABJs) consist of generally two joined components and the layer of adhesive between them [ 1 , 2 ]. The most important part of the ABJ is the adhesive itself, that is, the component depending mainly of the formulation, followed by the preparation process that precedes the application of the adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…Some estimations claim that over 20% of ABJ are used in construction (windows, doors, pipes, flooring, insulation, glazing, tiles, among others). However, other applications have emerged, such as those in the fields of electronics, energy, marine, automotive, and aerospace industries [ 2 , 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%